Konstruksi Metodologi Fiqh al-Bukhārī dan Kegagalan Pembentukan Mazhab - Muh. Fathoni Hasyim (Islamica: Jurnal Studi Keislaman, 2019)
The popularity of al-Bukhārī as the expert of ḥadīth is indisputable; he reached his top figure; his name becomes a guarantee of his ḥadīth validity; besides, he is also well-known as the expert of Islamic law (faqīh). However, his expertise in Islamic law is often disregarded. In fact, the authority of al-Bukhārī in Islamic law reaches its peak as an absolute mujtahid (mujtahid muṭṭlaq). This phenomenon raised some questions. Firstly, is al-Bukhārī affiliated with one of the established Sunnī madhhabs? When a mujtahid has reached his absolute rank, he needs his own fiqh methodology construction, other than following another methodology. Secondly, does al-Bukhārī have his own methodology? Frankly, an absolute mujtahid has an opportunity to establish his own madhhab ordained to his name. Thirdly, why is al-Bukhārī madhhab unpopular among Sunnī madhhabs? This article found that al-Bukhārī is not affiliated to certain madhhabs, then explored the methodology formation as well as other factors underlying the failure of formation of al-Bukhārī’s madhhab.